Penerapan Healing Architecture dalam Perancangan Pusat Rehabilitasi Mental di Kota Makassar - Fahlevi, Reza Ali; Ersina, Sriany; Abdullah, Sudarman (TIMPALAJA : Architecture Student Journals, 2025)
The mental health issues in the area, including Kota Makassar, indicate the need for rehabilitation facilities that can support the holistic development process due to social, lifestyle, and environmental changes. The purpose of this study is to investigate the concept and design of the Mental Rehabilitation Center in Makassar, using healing architecture that emphasizes alam, cahaya, warna, ruang scale, and user quality of inderawi. The method used is a qualitative descriptive method that involves studies of pustaka, lapangan, and pre-existing construction studies. These are then analyzed and interpreted to determine the concept of tapak, the mass of construction, and the pengolahan of the outside and inside. The results show that the tapak composition has about 37% building coverage and 63% terbuka hijau, with clear zones for private space, air, and river views, green roof installation at the main building, and lembut, terang, and human-centered interior design. Overall, it is hoped that the design will create a rehabilitation environment that not only meets functional medical needs but also provides a sense of aman, nyaman, and encouragement to support the patient's psychological recovery .